2018
DOI: 10.1042/bsr20171265
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29a: a potential therapeutic target and promising biomarker in tumors

Abstract: MiRNAs, small non-coding RNA molecules, were recognized to be associated with the incidence and development of diverse neoplasms. MiRNAs were small non-coding RNAs that could regulate post-transcriptional level by binding to 3′-UTR of target mRNAs. Amongst which, miR-29a was demonstrated that it had significant impact on oncogenicity in various neoplasms through binding to critical genes which enhanced or inhibited the progression of cancers. MiR-29a participated in kinds of physiological and pathological proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 97 publications
2
47
0
Order By: Relevance
“…In WT, there are few studies that have reported it; one of them evaluated its expression in eight serum samples from WT patients and in eight predominantly blastemal FHWT tumors, and in both cases, no changes in its expression were observed, likely due to a low sample number (3,31). In other tumors, its expression has been reported low as in renal cell carcinoma (32), lung cancer (33), and hepatocellular carcinoma (23); moreover, overexpression of this miRNA in these tumors inhibits cell proliferation, migration, and invasion, leading to it being characterized as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…In WT, there are few studies that have reported it; one of them evaluated its expression in eight serum samples from WT patients and in eight predominantly blastemal FHWT tumors, and in both cases, no changes in its expression were observed, likely due to a low sample number (3,31). In other tumors, its expression has been reported low as in renal cell carcinoma (32), lung cancer (33), and hepatocellular carcinoma (23); moreover, overexpression of this miRNA in these tumors inhibits cell proliferation, migration, and invasion, leading to it being characterized as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present study experimental animals were exposed to DMBA and the expression levels of miR-330, miR-29a, miR-9-1, miR-9-3 were examined. These miRNAs have already been reported to exhibit altered expression in several malignant tumors and through different signaling pathways they play a role in the regulation of oncogenes or tumor suppressor genes, cell growth, proliferation, invasion, migration, metastasis or apoptosis (21)(22)(23)(24)(25)(26). Besides the mentioned microRNAs, we also examined the expression of the mTORC1 gene.…”
mentioning
confidence: 99%
“…As a member of the miR-29 family, miR-29a is considered to play a crucial role in the regulation of multiple cancers ( Wang et al, 2018 ). It was up-regulated and promoted epithelial-mesenchymal transition, migration and invasion in breast cancer cells ( Wu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%